Behavioral Dynamics In Rainwater Harvesting Adoption: A Survey Of Bengaluru Residents - Subbarao, Madhuri; Singh, Reena (Journal of Neonatal Surgery, 2025)
Bengaluru, one of India’s fastest-growing urban centers, faces increasing water stress despite significant rainfall potential, highlighting the need for decentralized solutions such as rainwater harvesting (RWH). This study examines the behavioral dynamics influencing the acceptance, adoption, and sustained use of RWH among urban residents. Using a cross-sectional survey (N = 55), the study applies descriptive, correlational, and inferential analyses—including reliability testing, logistic regression, and factor analysis—to identify key drivers of adoption. The findings reveal a pronounced intention–action gap, with high levels of awareness and willingness (94%) contrasting sharply with low actual adoption (11%). Logistic regression indicates that awareness significantly increases the likelihood of adoption, while cost concerns act as a major deterrent. Perceived water scarcity shows only a moderate influence, suggesting that the absence of immediate crisis reduces behavioral urgency. Factor analysis identifies three underlying dimensions—economic–awareness, policy orientation, and sustainability—indicating fragmentation in decision-making processes. The results underscore that water conservation behavior is shaped not only by knowledge but also by cognitive, social, and economic factors, including risk perception, social norms, and financial constraints. The study concludes that effective RWH adoption requires integrated interventions that enhance perceived urgency, strengthen individual agency, and align policy enforcement with behavioral strategies. These findings contribute to the growing literature on urban sustainability by offering a behavioral framework for improving decentralized water management in rapidly urbanizing contexts..